Automated Requirement Dependency Analysis for Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Hieb, Michael; Preuß, Daniel (Proceedings of the Design Society)
Abstract Requirements changes are a leading cause for project failures. Due to propagation effects, change management requires dependency analysis. Existing approaches have shortcomings regarding ability to process large requirement sets, availability of required data, differentiation of propagation behavior and consideration of higher order dependencies. This paper introduces a new method for advanced requirement dependency analysis based on machine learning. Evaluation proves applicability and high performance by means of a case example, 4 development projects and 3 workshops with industry experts.

Mensch-Tracking zur Identifizierung des Voranschreitens von Roboterunterstützten Rettungseinsätzen der Feuerwehr - Gräßler, I.; Roesmann, Daniel; Pottebaum, Jens; Corves, Burkhard; Mandischer, Nils; Gürtler, Marius (Tagungsband der VDI Mechatronik 2022)

Extended RFLP for complex technical systems - Gräßler, Iris; Wiechel, Dominik; Oleff, Christian

Further Development of 3D Crack Growth Simulation Program to Include Contact Loading Situations - Joy, Tintu David; Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Applied Sciences)
Crack growth in structures depends on the cyclic loads applied on it, such as mechanical, thermal and contact, as well as residual stresses, etc. To provide an accurate simulation of crack growth in structures, it is of high importance to integrate all kinds of loading situations in the simulations. Adapcrack3D is a simulation program that can accurately predict the propagation of cracks in real structures. However, until now, this three-dimensional program has only considered mechanical loads and static thermal loads. Therefore, the features of Adapcrack3D have been extended by including contact loading in crack growth simulations. The numerical simulation of crack propagation with Adapcrack3D is generally carried out using FE models of structures provided by the user. For simulating models with contact loading situations, Adapcrack3D has been updated to work with FE models containing multiple parts and necessary features such as coupling and surface interactions. Because Adapcrack3D uses the submodel technique for fracture mechanical evaluations, the architecture of the submodel is also modified to simulate models with contact definitions between the crack surfaces. This paper discusses the newly implemented attribute of the program with the help of illustrative examples. The results confirm that the contact simulation in Adapcrack3D is a major step in improving the functionality of the program.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Influence of plane mixed-mode loading on the kinking angle of clinchable metal sheets - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Procedia Structural Integrity)
Keywords: General Engineering; Energy Engineering and Power Technology

A Review on the Modeling of the Clinching Process Chain - Part III: Operational Phase - Schramm, Britta; Harzheim, Sven; Weiß, Deborah; Joy, Tintu David; Hofmann, Martin; Mergheim, Julia; Wallmersperger, Thomas (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Development of a method for the separate measurement of the growth of internal crack tips by means of the potential drop method - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

A statistically based strain energy function for polymer chains in rubber elasticity - Mahnken, Rolf; Mirzapour, Jamil (Archive of Applied Mechanics)
Keywords: Mechanical Engineering

Effects on Process Forces of Individual Milling Tool Edges Depending on the Cutting Angle and Cutting Speed When Milling Cfrp - Clemens, Robin; Barth, Enrico; Uhlmann, Eckart; Zhan, Yingjie; Caylak, Ismail; Mahnken, Rolf (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Innendrückwalzen – Ein innovatives Umformverfahren zur inkrementellen Formgebung von wanddickenkonturierten Rohren mit lokal einstellbaren mechanischen Eigenschaften - Wiens, Eugen

Occupy the Internet: Why we need a Public Service Internet - Unterberger, Klaus; Fuchs, Christian (Building a European Digital Public Space: Strategies for Taking Back Control from Big Tech Platforms)

Social Media, Alienation, and the Public Sphere - Fuchs, Christian (The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media)

大数据、社交媒体和数字异化 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences) 2022 (5))

Servizio Pubblico - Fuchs, Christian (Wired Italia 102)

Digital Humanism. A Philosophy for 21st Century Digital Society. SocietyNow Series - Fuchs, Christian

Methodenentwicklung zur Auslegung geklebter Verbindungen aus hochfestem Stahl unter Berücksichtigung betriebsrelevanter Beanspruchungen im Landmaschinen- und Anlagenbau - Göddecke, Johannes; Meschut, Gerson; Göhrs, Tim; Große Gehling, Manfred

Dämpfungseigenschaften geklebter Strukturen unter dynamischer Beanspruchung - Göddecke, Johannes; Meschut, Gerson

Application of Thermal Neural Networks on a Small-Scale Electric Motor - Kirchgässner, Wilhelm; Wöckinger, Daniel; Wallscheid, Oliver; Bramerdorfer, Gerd; Böcker, Joachim (IKMT 2022; 13. GMM/ETG-Symposium)

Zu Online-Vergleichsportalen und deren Auswirkungen auf den Markt - Eine wettbewerbspolitische Analyse - Hensel, Jason

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Ecological validity in exercise neuroscience research: A systematic investigation - Chang, Melissa; Büchel, Daniel; Reinecke, Kirsten; Lehmann, Tim; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Triggering instabilities of polymer solution suspensions under uniaxial extension (Presentation) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Instability analysis of suspensions with a polymer solution matrix (Presentation) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Transform the Internet: Why we Need a Public Service Internet - Fuchs, Christian; Unterberger, Klaus (Public Value Texte)

Don’t Start from Scratch: A Modularized Architecture for Business Model Development Tools - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Software Business - 13th International Conference, ICSOB 2022, Bolzano, Italy, Proceedings)

Designing Platforms for Crowd-based Software Prototype Validation: A Design Science Study - Gottschalk, Sebastian; Parvez, Sarmad; Yigitbas, Enes; Engels, Gregor (Product-Focused Software Process Improvement - 23rd International Conference, PROFES 2022, Jyväskylä, Finland, Proceedings)

UCAI 2022 - 3rd International Workshop on User-Centered Artificial Intelligence - Buschek, Daniel; Hauptmann, Hanna; Heuer, Hendrik; Loepp, Benedikt; Riener, Andreas; Yigitbas, Enes (Proceedings of the Mensch Und Computer 2022 (MuC ’22))

Design and Evaluation of a Collaborative UML Modeling Environment in Virtual Reality - Yigitbas, Enes; Gorissen, Simon; Weidmann, Nils; Engels, Gregor (International Journal on Software and Systems Modeling (SoSyM))

Rezension zu: Michaela Eigmüller und Mathilde Wohlgemuth (Hrsg.): Schützen – Das Buch. 500 Jahre Kulturgeschichte in Süddeutschland, lllerbeuren 2021 - Leineweber, Jonas (Bayrisches Jahrbuch für Volkskunde)

Algorithms as complementary abstractions. Published online first 2022 - Matzner, Tobias (New Media & Society)

Hannah Arendt: Challenges of Plurality - Matzner, Tobias; Robaszkiewicz, Maria

Far-field Calculation from magnetic Huygens Box Data using the Boundary Element Method - Marschalt, Christoph; Schroder, Dominik; Lange, Sven; Hilleringmann, Ulrich; Hedayat, Christian; Kuhn, Harald; Sievers, Denis; Forstner, Jens (2022 Smart Systems Integration (SSI))

Detection of Defects on Irregularly Structured Surfaces using Supervised and Semi-Supervised Learning Methods - Sander, Tom; Lange, Sven; Hilleringmann, Ulrich; Geneis, Volker; Hedayat, Christian; Kuhn, Harald (2022 Smart Systems Integration (SSI))

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Flexible source of correlated photons based on LNOI rib waveguides - Ebers, Lena; Ferreri, Alessandro; Hammer, Manfred; Albert, Maximilian; Meier, Cedrik; Förstner, Jens; Sharapova, Polina R. (Journal of Physics: Photonics)
Lithium niobate on insulator (LNOI) has a great potential for photonic integrated circuits, providing substantial versatility in design of various integrated components. To properly use these components in the implementation of different quantum protocols, photons with different properties are required. In this paper, we theoretically demonstrate a flexible source of correlated photons built on the LNOI waveguide of a special geometry. This source is based on the parametric down-conversion (PDC) process, in which the signal and idler photons are generated at the telecom wavelength and have different spatial profiles and polarizations, but the same group velocities. Distinguishability in polarizations and spatial profiles facilitates the routing and manipulating individual photons, while the equality of their group velocities leads to the absence of temporal walk-off between photons. We show how the spectral properties of the generated photons and the number of their frequency modes can be controlled depending on the pump characteristics and the waveguide length. Finally, we discuss special regimes, in which narrowband light with strong frequency correlations and polarization-entangled Bell states are generated at the telecom wavelength.
Keywords: tet_topic_waveguide

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Flowability of polymer powders at elevated temperatures for additive manufacturing - Rüther, Moritz Johannes; Klippstein, Sven Helge; Schmid, Hans-Joachim

Mechanical joining in versatile process chains - Meschut, Gerson; Merklein, Marion; Brosius, Alexander; Bobbert, Mathias (Production Engineering)
The use of mechanical joining technologies offers the possibility of joining mixed material structures, which are used in particular in lightweight construction. An integrated securing of the joinability in versatile process chains is currently hardly possible as the number of combinable tool variants as well as variable force- and path-based process parameters is infinite. A versatile process chain, i.e. a sequence of all the processes and process steps required for product manufacturing, enables targeted changes to the semi-finished product, the joint, the component or the joining process that exceed the originally planned extend while still ensuring joinability. In detail, it leads to a unique joint with its own mechanical property profile, which, against the background of the resulting infinite number of combinations, makes it impossible to secure the joinability on the conventional experimentally based approach without extensive safety factors. The Transregional Colaborative Research Center 285 (TCRC285), which also initiated this special issue, is intended to enable mechanical joining technology to be versatile in the sense of high application flexibility. This is to be achieved with a numerical representation of the complete process chain from the incoming semi finished product via the joining part production and the joining process to the property profile of the joint in the operating phase. Thus a predictability of the joinability can be achieved and improvements in the individual life cycles of a joint can be realized by grasping the cause-and-effect relationships. On the basis of this knowledge, new possibilities for intervention in the joining process are to be created for the adaptation of the joining processes. With the aid of the methods developed for this purpose, tools will later be available to the end user to substitute the large number of mechanical joining processes or joining task-specific configurations with a smaller number of adaptable processes. This expands the flexibility in material choices, enabling challenges in environmental issues and sustainability to be overcome.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Untersuchung von Klebverbindungen für Batteriegehäuse - Schmolke, Tobias; Meschut, Gerson; Meinderink, Dennis; Rieker, Florian; Grundmeier, Guido (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Influence of the incident angle on the OCT measurement during remote laser beam welding - Werner, Matthias; Wagner, Jonas; Ribbeck, Florian; Hensel, Simon; Goth, Klaus; Graf, Thomas; Meschut, Gerson (Procedia CIRP)
Keywords: General Medicine

Thomas Nyckel, Isabel Schmiedel, und Florian Sprenger - Shnayien, Marie-Luise; Engemann, Christoph (The Lab Book. Situated Practices in Media Studies)

ROBOTER BAUEN, PROGRAMMIEREN LERNEN, DIGITALE KULTUREN VERSTEHEN — Christoph Engemann, Sylvia Kokot, Thomas Nyckel, Isabel Schmiedel, Mary Shnayien, Florian Sprenger über Arduino in medienwissenschaftlicher Lehre und Forschung - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (Open Media Studies Blog)
Die Sonderreihe zu Forschen, Lehren und Lernen mit digitalen Tools setzt sich mit zwei Beiträgen aus dem Bochumer Virtual Humanities Lab (VHL) fort. Im ersten Teil geht es um das auf Obsidian beruhende Laborbuch, das die Forschungsprozesse und Forschungsdaten am VHL dokumentiert, vernetzt und veröffentlicht. Explizites Ziel ist es, damit auch die Sackgassen, Wiederholungen und Umwege dieser Forschung sichtbar zu machen. Der zweite Teil stellt Arduino-Bausätze vor, wie sie am VHL in Forschung und Lehre eingesetzt werden, um in der Hands-on-Auseinandersetzung mit informatischen und ingenieurwissenschaftlichen Artefakten und Methoden einen erweiterten Zugang zu digitalen Kulturen zu eröffnen.

FORSCHUNG (BE-)SCHREIBEN — Christoph Engemann, Sylvia Kokot, Thomas Nyckel, Isabel Schmiedel, Mary Shnayien, Florian Sprenger über medienwissenschaftliche Laborbücher - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (Open Media Studies Blog)
Die Sonderreihe zu Forschen, Lehren und Lernen mit digitalen Tools setzt sich mit zwei Beiträgen aus dem Bochumer Virtual Humanities Lab (VHL) fort. Im ersten Teil geht es um das auf Obsidian beruhende Laborbuch, das die Forschungsprozesse und Forschungsdaten am VHL dokumentiert, vernetzt und veröffentlicht. Explizites Ziel ist es, damit auch die Sackgassen, Wiederholungen und Umwege dieser Forschung sichtbar zu machen. Der zweite Teil stellt Arduino-Bausätze vor, wie sie am VHL in Forschung und Lehre eingesetzt werden, um in der Hands-on-Auseinandersetzung mit informatischen und ingenieurwissenschaftlichen Artefakten und Methoden einen erweiterten Zugang zu digitalen Kulturen zu eröffnen.

Arduino - Engemann, Christoph; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (The Lab Book. Situated Practices in Media Studies)

FORSCHUNG (BE-)SCHREIBEN - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Marie-Luise; Sprenger, Florian (Open Media Studies)

Benachteiligtenförderung - Heisler, Dietmar; Schemmer, Susanne (Psychische Belastungen in der Berufsbiografie. Interdisziplinäre Perspektiven.)
Eine Ausbildung meistern, am Erwerbsleben teilnehmen: Das ist angesichts psychischer Belastungen sehr herausfordernd. Und auch für die begleitenden Pädagoginnen und Pädagogen erwächst aus den vielfältigen Symptomatiken die Aufgabe, Unterstützungsmaßnahmen individuell zu gestalten. In dem interdisziplinär angelegten Band wird psychische Belastung erstmals als Querschnittsphänomen aus unterschiedlichen Fachperspektiven betrachtet. Autorinnen und Autoren aus Berufspädagogik, Sonderpädagogik, Sozialpädagogik, Psychologie und Sozialpsychiatrie diskutieren die nachschulischen beruflichen Bildungsprozesse und Unterstützungsangebote zur Teilhabe am Erwerbsleben.

Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern
Über zwei Jahre prägte die Corona-Pandemie unser Leben. Auch für die Berufsbildung blieb das nicht ohne Konsequenzen. Rückblickend wird die Pandemie als „Brennglas“ bezeichnet, in dem sich die Herausforderungen des Bildungswesens bündelten und zeigten. Die Beiträge des vorliegenden Bandes befassen sich mit den konkreten Folgen der Pandemie für verschiedene Bereiche beruflicher Bildung. Ein weiterer Fokus liegt auf der Gestaltung und Wirkung des Distanzlernens in Schule, Betrieb und Hochschule. Zentrale Entwicklungen und ihre Effekte werden bilanziert und reflektiert. Die Beiträge des vorliegenden Bandes benennen nicht nur Desiderate und Schwächen im System beruflicher Bildung, sondern weisen auch auf Chancen und Potenziale hin.
Keywords: Pandemie; Homeschooling; Digitalisierung; Ausbildung; Distanzlernen

Gebäude und Lernumgebungen von Pflegeschulen in Thüringen und Nordrhein-Westfalen - Heisler, Dietmar (Handbuch: Gebäude Berufsbildender Schulen)
Im Handbuch steht die räumliche Gestaltung Berufsbildender Schulen im Fokus. Mit rund 3500 Gebäuden repräsentieren Berufsbildende Schulen in Deutschland ihre besondere berufsorientierte Ausbildungsform. Aber auch in dieser Schulform spielt das Thema Lernraumgestaltung als „dritter Pädagoge" eine zunehmend wichtige Rolle. Trotzdem wird der Neu- und Umbau Berufsbildender Schulgebäude nur selten zwischen Planenden, Lehrenden und Lernenden diskutiert. Um diese Lücke zu schließen, verknüpfen die über 70 Autoren und Autorinnen des Sammelbandes architektonische, Berufsbildungs- und lernorganisatorische Aspekte zu einem neuen Ansatz für eine interdisziplinäre und integrative Planung dieses Lernraums. Im Zentrum des Bandes stehen insbesondere die Möglichkeiten des Zusammenwirkens von Architektinnen und Architekten, Lehrkräften und Lernenden.

Schulbauten aus Sicht der Beruflichen Fachrichtung Körperpflege - Heisler, Dietmar (Handbuch: Gebäude Berufsbildender Schulen)
Im Handbuch steht die räumliche Gestaltung Berufsbildender Schulen im Fokus. Mit rund 3500 Gebäuden repräsentieren Berufsbildende Schulen in Deutschland ihre besondere berufsorientierte Ausbildungsform. Aber auch in dieser Schulform spielt das Thema Lernraumgestaltung als „dritter Pädagoge" eine zunehmend wichtige Rolle. Trotzdem wird der Neu- und Umbau Berufsbildender Schulgebäude nur selten zwischen Planenden, Lehrenden und Lernenden diskutiert. Um diese Lücke zu schließen, verknüpfen die über 70 Autoren und Autorinnen des Sammelbandes architektonische, Berufsbildungs- und lernorganisatorische Aspekte zu einem neuen Ansatz für eine interdisziplinäre und integrative Planung dieses Lernraums. Im Zentrum des Bandes stehen insbesondere die Möglichkeiten des Zusammenwirkens von Architektinnen und Architekten, Lehrkräften und Lernenden.

"Die sehen mich als irgendwas zwischen Schulsozialarbeiter und Sonderpädagoge" - Ergebnisse einer Interviewstudie zur Rolle pädagogischer Fachkräfte in multiprofessionellen Teams an inklusive Schulen - Grüter, Sandra; Hölz, Svenja; Neumann, Phillip; Lütje-Klose, Birgit (Zeitschrift für Inklusion)
Keywords: Multiprofessionelle Teams; Kooperation; Professionalisierung; Schulentwicklung; Inklusion

Boosting artificial intelligence in design processes by the use of additive manufacturing - Ott, Manuel; Meihöfener, Niclas; Koch, Rainer (Proceedings of the 33rd Annual International Solid Freeform Fabrication Symposium 2022)
Additive manufacturing offers the option of converting digital prototypes into real structures as quickly as possible by the special property of tool-free manufacturing. However, this process can only be used at optimum speed if bottlenecks can be effectively avoided. One of these constraints is the design process. Although modern CAD systems allow a significant increase in many areas, this always requires a person with specific skills (e.g. engineer). In the field of AM in particular, more and more powerful software solutions have recently been published which accelerate the Design for Additive Manufacturing, including most CAD-tasks. In many areas, therefore, attempts are already made to automate relevant design steps as much as possible, more and more using neural networks and artificial intelligence. This paper presents how and why such techniques can be used to generate three-dimensional structures quickly and efficiently in cases of deep generative design tasks.

A novel correction method for the shear rate in a couette rheometer (Vortrag) - Rüther, Torben; Jesinghausen, Steffen; Schmid, Hans-Joachim
Keywords: Couette; Rheology; Correction

Multidimensional particle characterization: Centrifugal Differential Mobility Analyzer (Poster) - Rüther, Torben; Schmid, Hans-Joachim

NEW CORRECTION APPROACHES FOR DETERMINING THE TRUE SHEAR RATE IN A COAXIAL-RHEOMETER (Vortrag) - Rüther, Torben; Jesinghausen, Steffen; Schmid, Hans-Joachim

Chow groups of orders in number fields - Kirschmer, Markus; Klüners, Jürgen

RadioML Meets FINN: Enabling Future RF Applications With FPGA Streaming Architectures - Jentzsch, Felix; Umuroglu, Yaman; Pappalardo, Alessandro; Blott, Michaela; Platzner, Marco (IEEE Micro)
Deep neural networks (DNNs) are penetrating into a broad spectrum of applications and replacing manual algorithmic implementations, including the radio frequency communications domain with classical signal processing algorithms. However, the high throughput (gigasamples per second) and low latency requirements of this application domain pose a significant hurdle for adopting computationally demanding DNNs. In this article, we explore highly specialized DNN inference accelerator approaches on field-programmable gate arrays (FPGAs) for RadioML modulation classification. Using an automated end-to-end flow for the generation of the FPGA solution, we can easily explore a spectrum of solutions that optimize for different design targets, including accuracy, power efficiency, resources, throughput, and latency. By leveraging reduced precision arithmetic and customized streaming dataflow, we demonstrate a solution that meets the application requirements and outperforms alternative FPGA efforts by 3.5x in terms of throughput. Against modern embedded graphics processing units (GPUs), we measure >10x higher throughput and >100x lower latency under comparable accuracy and power envelopes.

Johann Rist / Thomas Selle: Neue musikalische Fest-Andachten (1655). Kritisch hg. u. kommentiert v. Johann Anselm Steiger, Berlin/Boston 2020 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Esther Wipfler (Hg.), Das Gesangbuch und seine Bilder. Voraussetzungen, Gestaltung, Wirkung, Wien u.a. 2020 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Tersteegen meets Jazz … Felicia singt: Tersteegen. CD von Felicia Friedrich, Mülheim 2021 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Bound state solutions of Dirac equation: spin and pseudo-spin symmetry in the presence of the combined Manning–Rosen and Yukawa tensor potentials - Ahmadov, A. I.; Nagiyev, Sh. M.; Aydin, C.; Tarverdiyeva, V. A.; Orujova, M. Sh.; Badalov, S. V. (The European Physical Journal Plus)
Keywords: General Physics and Astronomy; Fluid Flow and Transfer Processes

Sprache(n) im kindilchen Aneignungsprozess von (Medien-)Welt. Zur Relevanz der lebensweltlichen Mehrsprachigkeit von Kindergartenkindern aus Einwandererfamilien und mit einem deutsch-türkischen Hintergrund - Günesli, Habib (Mehrsprachigkeit und -kulturaltiät im Konflikt)
Dieser Beitrag basiert auf den Ergebnissen eines im Jahr 2019 abgeschlossenen Promotionsvorhabens im Rahmen des interventiv angelegten, in Dortmund angesiedelten, Forschungsprojekts KidSmart – Medienkompetent zum Schulübergang zu den Mediensozialisationserfahrungen von deutschen, deutsch-türkischen und deutsch-anderen vier und fünf Jahre alten Mädchen und Jungen in den sozialen Feldern Familie und KiTa. Im vorliegenden Beitrag werden die Angaben der Eltern, die mittels halbstandardisierter Fragebögen, und die Aussagen ihrer Kinder, die anhand der Puppet-Interview-Methode gewonnen werden konnten, fokussiert. Vor dem Hintergrund einer globalen und damit zunehmend (sozio-kulturell und sprachlich) pluralen und mediatisierten Welt wird gefragt, inwieweit und wie Kindern in ihrem Aneignungsprozess von (Medien-)Welt die Relevanz ihrer migrationsbedingten Mehrkulturalität und Mehrsprachigkeit vermittelt wird? Es stellte sich heraus, dass migrantisch mehrsprachige und im Besonderen deutsch-türkische Kinder zunächst und hauptsächlich ein- und deutschsprachige Mediennutzer*innen sind, weshalb sie, so ist zu vermuten, auch eine primär ein- und deutschsprachige Aneignung von (Medien-)Welt erfahren werden – insbesondere dann, wenn für sie die Relevanz ihrer Herkunfts- und Erstsprachen nicht ersichtlich ist. Ausgehend von diesen Ergebnissen wird im Rahmen dieses Beitrags perspektivisch nach der Bedeutung und Relevanz der Medienpädagogik zur Förderung der migrationsbedingten Mehrsprachigkeit gefragt und der Blick konkret auf die mehrkulturelle Mediensozialisationsforschung gerichtet, die diese Ausprägung der Mehrsprachigkeit zu ihrem zentralen Forschungsgegenstand machen sollte.
Keywords: Mehrsprachigkeit; Mehrkulturalität; Migration; Mediensozialisation; Migration; Frühe Bildung

Small-scale online simulations in guided-wave photonics - Hammer, Manfred (Integrated Optics: Devices, Materials, and Technologies XXVI)
Online solvers for a series of standard 1-D or 2-D problems in integrated optics will be discussed. Implemented on the basis of HTML/JavaScript/SVG with core routines compiled from well tested C++-sources, the quasi-analytical algorithms require a computational load that can be handled easily even by current mobile devices. So far the series covers the 1-D guided modes of dielectric multilayer slab waveguides and the oblique plane wave reflection from these, the modes of rectangular channel waveguides (in an approximation of effective indices), bend modes of curved multilayer slabs, whispering-gallery resonances (“Quasi-Normal-Modes”) supported by circular dielectric cavities, the hybrid modes of circular multi-step-index optical fibers, bound and leaky modes of 1-D complex multilayers, including plasmonic surface modes, and, with restrictions, quite general rectangular scattering problems in 2-D.
Keywords: tet_topic_waveguide

The “black box” of social commerce platforms-a closer look at users’ activities - Meydani, Elnaz; Düsing, Christoph; Fedrau, Annamaria; Trier, Matthias

Wie die Queen: Die deutsch-jüdische Geschichte einer sehr britischen Schriftstellerin - Ribbat, Christoph

Quasiparticle energies and optical response of RbTiOPO4 and KTiOAsO4 - Neufeld, Sergej; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
Many-body perturbation theory based on density-functional theory calculations is used to determine the quasiparticle band structures and the dielectric functions of the isomorphic ferroelectrics rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenide (KTiOAsO4). Self-energy corrections of more than 2 eV are found to widen the transport band gaps of both materials considerably to 5.3 and 5.2 eV, respectively. At the same time, both materials are characterized by strong exciton binding energies of 1.4 and 1.5 eV, respectively. The solution of the Bethe-Salpeter equation based on the quasiparticle energies results in onsets of the optical absorption within the range of the measured data.

Clean and Hydrogen‐Adsorbed AlInP(001) Surfaces: Structures and Electronic Properties - Glahn, Luis Joel; Ruiz Alvarado, Isaac Azahel; Neufeld, Sergej; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Ostheimer, David; Shekarabi, Sahar; Romanyuk, Oleksandr; Moritz, Dominik Christian; Hofmann, Jan Philipp; Jaegermann, Wolfram; Hannappel, Thomas; et al. (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Water/InP(001) from Density Functional Theory - Ruiz Alvarado, Isaac Azahel; Schmidt, Wolf Gero (ACS Omega)
Keywords: General Chemical Engineering; General Chemistry

P-Terminated InP (001) Surfaces: Surface Band Bending and Reactivity to Water - Moritz, Dominik Christian; Ruiz Alvarado, Isaac Azahel; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Frieß, Tilo; Runge, Erich; Hofmann, Jan P.; Hannappel, Thomas; Schmidt, Wolf Gero; Jaegermann, Wolfram (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Reconstructions of the As-Terminated GaAs(001) Surface Exposed to Atomic Hydrogen - Karmo, Marsel; Ruiz Alvarado, Isaac Azahel; Schmidt, Wolf Gero; Runge, Erich (ACS Omega)
Keywords: General Chemical Engineering; General Chemistry

Programmierung und Computersimulationen - Schindlmayr, Arno (Kompetent Prüfungen gestalten: 60 Prüfungsformate für die Hochschullehre)
Dieses Format eignet sich, um zu prüfen, inwieweit Studierende Computersimulationen und eigene kleine Programme zur Lösung typischer Probleme ihres Fachs nutzen können. Wie bei Klausuren erfolgt die Bearbeitung in begrenzter Zeit und unter Aufsicht, wird aber am Computer durchgeführt und beinhaltet neben der Programmierung auch vor- und nachbereitende Aufgaben im Kontext der fachlichen Anwendung.

Direct Measurement of Higher-Order Nonlinear Polarization Squeezing - Prasannan, Nidhin; Sperling, Jan; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Protonation-induced charge transfer and polaron formation in organic semiconductors doped by Lewis acids - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (RSC Advances)
Lewis-acid doping of organic semiconductors (OSCs) opens up new ways of p-type doping and has recently become of significant interest.
Keywords: General Chemical Engineering; General Chemistry

Tilting nondispersive bands in an empty microcavity - Gao, Ying; Li, Yao; Ma, Xuekai; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Microscopic Study of Molecular Double Doping - Bathe, Thomas; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry A)
Keywords: Physical and Theoretical Chemistry

Electron–Nuclear Coherent Coupling and Nuclear Spin Readout through Optically Polarized VB– Spin States in hBN - Murzakhanov, Fadis F.; Mamin, Georgy Vladimirovich; Orlinskii, Sergei Borisovich; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur; Aharonovich, Igor; Gottscholl, Andreas; Sperlich, Andreas; Dyakonov, Vladimir; Soltamov, Victor A. (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

The Impact of Product Differentiation on Retail Bundling in a Vertical Market - Endres-Fröhlich, Angelika Elfriede; Hehenkamp, Burkhard; Heinzel, Joachim
We study the effects of product differentiation on the bundling incentives of a two-product retailer. Two monopolistic manufacturers each produce a differentiated good. One sells it to both retailers, while the other only supplies a single retailer. Retailers compete in prices. Retail bundling is profitable when the goods are close substitutes. Only then is competition so intense that the retailer uses bundling to relax competition both within and across product markets, despite an aggravation of the double marginalization problem. Our asymmetric market structure arises endogenously for the case of close substitutes. In this case, bundling reduces social welfare.
Keywords: Retail bundling; upstream market power; double marginalization; product differentiation

Modellierung des Stofftransportes in einer geneigten Kolonne mit dem Ansatz der hydrodynamischen Analogien - Ehlert, Thomas; Mamedov, Tural; Schubert, Markus; Kenig, Eugeny Y.

Electrochemical performance of KTiOAsO_4 (KTA) in potassium-ion batteries from density-functional theory - Bocchini, Adriana; Gerstmann, Uwe; Bartley, Tim; Steinrück, Hans-Georg; Henkel, Gerald; Schmidt, Wolf Gero (Phys. Rev. Materials)

Oxygen vacancies in KTiOPO_4: Optical absorption from hybrid DFT - Bocchini, Adriana; Gerstmann, Uwe; Schmidt, Wolf Gero (Phys. Rev. B)

Transareales Gedenken an genozidale Geschichte in Analogie zum islamistischen Terror der Gegenwart in "Das Dorf" des algerischen Autors Boualem Sansal" - Müller, Inez

Experimental Demonstration of a 2.2kW Active-Clamp Converter for High-Current Wide-Voltage-Transfer Ratio Applications - Rehlaender, Philipp; Korthauer, Bastian; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Phase-Shift Modulation for Flying-Capacitor DC-DC Converters - Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Development of a Hybrid Modeling Methodology for Oscillating Systems with Friction - Wohlleben, Meike Claudia; Bender, Amelie; Peitz, Sebastian; Sextro, Walter (Machine Learning, Optimization, and Data Science)

Analysis of the Segregation Phenomena of Wood Fiber Reinforced Plastics - Moritzer, Elmar; Flachmann, Felix; Richters, Maximilian; Neugebauer, Marcel (Journal of Composites Science)
Wood–plastic composites (WPC) are enjoying a steady increase in popularity. In addition to the extrusion of decking boards, the material is also used increasingly in injection molding. Depending on the formulation, geometry and process parameters, WPC tends to exhibit irregular filling behavior, similar to the processing of thermosets. In this work, the influence of matrix material and wood fiber content on the flow, mold filling and segregation behavior of WPC is analyzed. For this purpose, investigations were carried out on a flow spiral and a sheet cavity. WPC based on thermoplastic polyurethane (TPU) achieves significantly higher flow path lengths at a wood mass content of 30% than polypropylene (PP)-based WPC. The opposite behavior occurs at higher wood contents due to the different shear thinning behavior. Slightly decreased wood contents could be observed at the beginning of the flow path and greatly increased wood contents at the end of the flow path, compared to the starting material. When using the plate cavity, flow anomalies in the form of free jets occur as a function of the wood content, with TPU exhibiting the more critical behavior. The flow front is frayed, but in contrast to the flow spiral, no significant wood accumulation could be detected due to the shorter flow path lengths.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Dynamic modeling of absorption/desorption closed-loop including periphery - Bothe, Mike; Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny Y. (Computers and Chemical Engineering)

Institutionen der Medienpädagogik. Erwachsenen- und Weiterbildung - Meister, Dorothee M.; Dehmel, Lukas (Handbuch Medienpädagogik.)

Joining of multi-material structures using a versatile self-piercing riveting process - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Lechner, Michael; Meschut, Gerson (Production Engineering)
Due to the increasing use of multi-material constructions and the resulting material incompatibilities, mechanical joining technologies are gaining in importance. The reasons for this are the variety of joining possibilities as well as high load-bearing capacities. However, the currently rigid tooling systems cannot react to changing boundary conditions, such as changed sheet thicknesses or strength. For this reason, a large number of specialised joining processes have been developed to expand the range of applications. Using a versatile self-piercing riveting process, multi-material structures are joined in this paper. In this process, a modified tool actuator technology is combined with multi-range capable auxiliary joining parts. The multi-range capability of the rivets is achieved by forming the rivet head onto the respective thickness of the joining part combination without creating a tooling set-up effort. The joints are investigated both experimentally on the basis of joint formation and load-bearing capacity tests as well as by means of numerical simulation. It turned out that all the joints examined could be manufactured according to the defined standards. The load-bearing capacities of the joints are comparable to those of conventionally joined joints. In some cases the joint fails prematurely, which is why lower energy absorptions are obtained. However, the maximum forces achieved are higher than those of conventional joints. Especially in the case of high-strength materials arranged on the die side, the interlock formation is low. In addition, the use of die-sided sheets requires a large deformation of the rivet head protrusion, which leads to an increase in stress and, as a result, to damage if the rivet head. However, a negative influence on the joint load-bearing capacity could be excluded.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Provision of cross-domain knowledge in mechanical joining using ontologies - Zirngibl, Christoph; Kügler, Patricia; Popp, Julian; Bielak, Christian Roman; Bobbert, Mathias; Drummer, Dietmar; Meschut, Gerson; Wartzack, Sandro; Schleich, Benjamin (Production Engineering)
Since the application of mechanical joining methods, such as clinching or riveting, offers a robust solution for the generation of advanced multi-material connections, the use in the field of lightweight designs (e.g. automotive industry) is steadily increasing. Therefore, not only the design of an individual joint is required but also the dimensioning of the entire joining connection is crucial. However, in comparison to thermal joining techniques, such as spot welding, the evaluation of the joints’ resistance against defined requirements (e.g. types of load, minimal amount of load cycles) mainly relies on the consideration of expert knowledge, a few design principles and a small amount of experimental data. Since this generally implies the involvement of several domains, such as the material characterization or the part design, a tremendous amount of data and knowledge is separately generated for a certain dimensioning process. Nevertheless, the lack of formalization and standardization in representing the gained knowledge leads to a difficult and inconsistent reuse, sharing or searching of already existing information. Thus, this contribution presents a specific ontology for the provision of cross-domain knowledge about mechanical joining processes and highlights two potential use cases of this ontology in the design of clinched and pin joints.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Investigation of the friction conditions of self-pierce rivets by means of a compression-torsion tribometer - Rossel, Moritz Sebastian; Meschut, Gerson (Production Engineering)
Lightweight design is an effective lever for achieving fuel consumption and emission-oriented goals. Therefore micro-alloyed steels and high-strength aluminium materials are included in the multi-material mix of the car body. In this context self-pierce riveting has become established for joining in body-in-white production. For the dimensioning of the joint, numerical simulation is increasingly being used. In order to make reliable predictions about joint quality, knowledge of the friction in the joining process is necessary and needs to be identified experimentally. In previous investigations, the process parameters in the friction test were not comparable to the joining process. Therefore, a new friction test method is presented in this paper, where the process conditions are comparable between joining and friction testing especially regarding the interface pressure. The local joining process parameters between rivet and sheet are derived numerically. In the framework of the investigations, the influences of the local joining process parameters, like interface pressure, relative velocity and temperature, on the friction are investigated and mapped close to the joining process. Additionally a comparison of different rivet coatings is carried out. The rivet contact to the sheet metal HX340LAD as well with aluminium EN AW-5182 is taken into account.

Numerical Investigation of the Influence of a Movable Die Base on Joint Formation in Semi-tubular Self-piercing Riveting - Kappe, Fabian; Wituschek, Simon; de Pascalis, Vincenzo; Bobbert, Mathias; Lechner, Michael; Meschut, Gerson (Materials Design and Applications IV)
Due to economic and ecological requirements and the associated trend towards lightweight construction, mechanical joining technologies like self-piercing riveting are gaining in importance. In addition, the increase in lightweight multi-material joints has led to the development of many different mechanical joining technologies which can only be applied to join a small number of material combinations. This leads to low process efficiency, and in the case of self-piercing riveting, to a large number of required tool changes. Another approach focuses on reacting to changing boundary conditions as well as the creation of customised joints by using adaptive tools, versatile auxiliary joining parts or modified process kinematics. Therefore, this study investigates the influence of increased die-sided kinematics on joint formation in self-piercing riveting process. The aim is to achieve an improvement of the joint properties by superimposing the punch feed. Furthermore, it is intended to reduce required tool changes due to the improved joint design. The investigations were carried out by means of a 2D-axisymmetric numerical simulation model using the LS-Dyna simulation software. After the validation of the process model, the die was extended to include driven die elements. Using the model, different kinematics as well as their effects on the joint formation and the internal stress concentration could be analysed. In principle, the increased actuator technology enabled an increase of the interlock formation for both pure aluminium and multi-material joints consisting of steel and aluminium. However, the resulting process forces were higher during the process phases of punching and spreading.

Determining the influence of different process parameters on the versatile self-piercing riveting process using numerical methods - Kappe, Fabian; Zirngibl, Christoph; Schleich, Benjamin; Bobbert, Mathias; Wartzack, Sandro; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management

Increasing flexibility of self-piercing riveting by reducing tool–geometry combinations using cluster analysis in the application of multi-material design - Kappe, Fabian; Schadow, Luca; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers Part L Journal of Materials Design and Applications)

Determining the properties of multi‑range semi‑tubular self‑piercing riveted joints - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Meschut, Gerson (Production Engineering)

Literature study on the potential of Artificial Intelligence in Scenario-Technique - Gräßler, Iris; Tusek, Alena Marie; Thiele, Henrik; Preuß, Daniel; Grewe, Benedikt; Hieb, Michael (XXXIII ISPIM Innovation Conference Proceedings)

NTFA-enabled goal-oriented adaptive space–time finite elements for micro-heterogeneous elastoplasticity problems - Ju, X.; Mahnken, Rolf; Xu, Y.; Liang, L. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

A polymorphic uncertainty model for the curing process of transversely fiber-reinforced plastics - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (Mathematics and Mechanics of Complex Systems)
Keywords: Computational Mathematics; Numerical Analysis; Civil and Structural Engineering

New low order Runge–Kutta schemes for asymptotically exact global error estimation of embedded methods without order reduction - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Efficient Extraction of Technical Requirements Applying Data Augmentation - Gräßler, Iris; Preuß, Daniel; Brandt, Lukas; Mohr, Michael (Proceedings of 8th IEEE International Symposium on Systems Engineering 2022)

Gestaltung einer Forschungsinfrastruktur für die Anwendung digitaler Werkzeuge in Cyber-Physischen Produktionssystemen - Gräßler, Iris; Hieb, Michael; Roesmann, Daniel (Automation 2022)